18F-FDG PET/CT for invasive fungal infection in immunocompromised patients - Benjamin Leroy‐Freschini; Giorgio Treglia; X. Argémi; Caroline Bund; Romain Kessler; Raoul Herbrecht; Alessio Impériale (2018)
Opportunistic invasive fungal infections (IFIs) comprise a heterogeneous spectrum of pathogens, whose early diagnosis remains challenging. Candida spp. and Aspergillus spp, the most frequent pathogens in immunocompromised patients, frequently affect lungs, liver, bone and skin.To evaluate the impact of 18F-FDG PET/CT in the management of immunocompromised patients with IFI.A single-center retrospective study included 51 immunocompromised patients with IFI diagnosis undergoing 83 18F-FDG PET/CTs.Twenty-nine 18F-FDG PET/CTs were performed for primary work-up in 29 treatment-naïve patients. Fifty-four PET/CTs were performed during follow-up to confirm IFI suspicion in 22 patients who had anti-fungal drug therapy before PET/CT. When available, histological and/or microbiological criteria were used to assess IFI diagnosis.Aspergillus spp. and Candida spp. were the most frequent microorganisms responsible for IFI in our population. 18F-FDG PET/CT sensitivity, specificity, positive and negative predictive values, and global accuracy were 93%, 81%, 95%, 72% and 90%, respectively. 18F-FDG PET/CT influenced the diagnostic work-up at primary staging in 16/29 patients (55%) by assessing the extent of infection and targeting the diagnostic procedure. 18F-FDG PET/CT results during treatment induced anti-fungal drugs dosage increase and/or new drugs addition in 8/54 cases (15%) and contributed to the reduction of anti-fungal drugs dosage or treatment withdraws in 17 cases (31%).We recommend the utilization of 18F-FDG PET/CT to improve the primary staging work-up of immunocompromised patients with IFI and to assess treatment effectiveness or disease relapse. Both 18F-FDG PET/CT and conventional imaging should be integrated into a well-defined imaging diagnostic algorithm considering the clinical context and both strengths and limitations of each diagnostic modality.